Antioxidant characterization of new dietary fiber concentrates from papaya pulp and peel (Carica papaya L.) - Nieto Calvache, Jhon Edinson (2016)
Residues of papaya pulp and peel were used to produce dietary fiber concentrates (DFCs) by treatment with ethanol and microwave drying. The fiber showed antioxidant capacity. Phenolics, carotenoids and ascorbic acid were detected. Chromatographic analysis allowed the identification of five phenolic compounds: protocatechuic acid hexoside, manghaslin, quercetin 3-O-rutinoside, caffeoyl hexoside and ferulic acid. Likewise, lutein, zeaxanthin, β-carotene and β-criptoxanthin were identified and quantified by HPLC. Finally, an analysis of digestibility showed that about 65% of the polyphenols associated to pulp and peel DFCs were potentially bioaccessible in the small intestine and that the portion of indigestible fiber had antioxidant capacity. The DFCs produced have the capacity for acting as a functional ingredient of application in the food industry, for helping to prevent the oxidation of lipids or also to meet the demand of the food market concerning the development of food with health protection capacity.